ICT in Structured Programming Learning through Constructivist Techniques for Education - García Torres, Ingrid; Plaza Vargas, Angel; Zurita Hurtado, Harry (Journal of Science and Research, 2018)
There are some things for university students that are important to acquire the whole learning of a particular subject moreover when the subject is one of the last ones that a student must take in order to finish the university requirements to be a professional, at the moment the student has a wide range of knowledge and he is almost ready to begin his professional life. In the process of learning Structured Programming, it is necessary the use of teaching techniques that let students get thoroughly involved in building programs efficiently. This is the case of pedagogical focus based on the constructivism methodology with a pedagogical strategy solving problems and learning with a metacognition orientation based on the successful education for Structured Programming specifically, using programming languages like C ++, Visual Basic 6, Visual Basic Net, hypertext protocol, Java, among others. It should be mentioned that the main objective of this research is to develop a study with Learning Methodologies for Structured Programming using constructivist techniques. The specific objectives are based on establishing teaching events in the processes of meaningful learning of students; defining the percentage that teachers involved technologies in their classroom processes in terms of programming, classifying teachers into levels of knowledge about using constructivist programming technologies for teaching. Teachers should positively have as a part of his pro le the knowledge of ICT in terms of software creation and the use of methodologies and resources doing teachers’ role.